Assessing the Influence of Control and Motivation on Teacher’s Effectiveness in Some Government Secondary Schools in the Centre Region of Cameroon. - Jennet, Deba Nkongho; Oben, Agbor Emmanuel (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2026)
The study on Assessing the influence of Control and Motivation on Teacher’s Effectiveness in Some Government Secondary Schools in the Centre Region of Cameroon had as general objective to investigate the extent to which control and motivation can influence teachers’ effectiveness in some Government Secondary Schools in the Centre Region of Cameroon. The study had as main research question, what is the influence of Control and Motivation on Teachers’ Effectiveness in some Government Secondary Schools in the centre Region of Cameroon? The study was guided by a general research hypothesis that stated that control and motivation do not have any statistically significant influence on teachers’ effectiveness in Government Secondary Schools in the Centre Region of Cameroon. The study made use of two theoretical assumptions: Herzberg’s two factor theory and McGregor’s theory X and Y. Making use of a quantitative research method with a descriptive survey design, data was collected with the help of a structured questionnaire from seven selected schools. With a total of three hundred and three (303) teachers selected through the simple random technique. The data collected for this research was analysed using descriptive and inferential statistics. The hypotheses for this study were tested with the help of simple linear regression. The research findings revealed that principals’ controlling functions has a significant relationship with teacher’s effectiveness, while principals’ motivating functions, showed no statistically significant relationship with Teacher’s effectiveness. Based on the findings of the study, it was recommended that Government should introduce management courses in the curriculum of the Higher Teachers Training Colleges in the country to prepare future school administrator with the require management functions such as control, motivation, planning, coordinating, supervision... just to name these few.